INSTRUMENTAL DIAGNOSTIC OF CARDIAC DISORDERS DUE TO INFECTIOUS DISEASES - V. B. Voitenkov; S. N. Chuprova; I. V. Babachenko; E. V. Sharipova; N. V. Skripchenko (Журнал инфектологии, 2018)
In our review we present update on modern state of knowledge on instrumental methods of heart function evaluation. This methods are valuable and reliable additional tool in diagnostic process in patients with infectious diseases of different origins. Electrocardiography and heart ultrasound allows to perform noninvasive and highly informative investigation of heart’s condition on all stages of the disease. We review both literature and our own data on these matters. Heart MRI may further improve that diagnostic process and add it with valuable insights into the heart function and anatomy during the infectious diseases.